Synthesis and Evaluation of New 3-Substituted[3,4-dihydro pyrimidinones]indolin-2-ones for Antioxidant Activity - AJITHA, M.; RAJNARAYANA, K.; SARANGAPANI, M. (Asian Journal of Chemistry, 2010)
New 3-substituted[3,4-dihydropyrimidinones]indolin-2-ones have been synthesized and tested for antioxidant activity by UV spectrophotometer and HPLC method. Among them compounds C16, C15, C14, C13 and C12 exhibited higher antioxidant activity. However, these antioxidant activities are lower than ascorbic acid. Antioxidant activities are performed both UV-Vis spectrometer and reverse phase HPLC methods, both the methods were compared and found 2 to 5 % variation were observed. HPLC method is more sensitive and suitable for the said compounds than UV-Vis spectrometer.